Respuesta :

LukeG1

Answer:

6

Step-by-step explanation:

8x + 22 = 19x

Subtract 8x from both sides of the equation

22 = 11x

Divide both sides of the equation by 11

x = 2

Multiply both sides of the equation by 3

3x = 6

Hope this helps :)

Answer:

6

Step-by-step explanation:

Step 1:  Subtract 22 from both sides

8x + 22 - 22 = 19x - 22

8x = 19x - 22

Step 2:  Subtract 19x from both sides

8x - 19x = -22 + 19x - 19x

-11x = -22

Step 3:  Divide both sides by -11

-11x / -11 = -22 / -11

x = 2

Step 4:  Find 3x

3x

3(2)

6

Answer:  6

ACCESS MORE